General level of compliance on internal auditors’ code of ethics in five Malaysian listed government linked companies / Noor Furzanne Alias - Alias, Noor Furzanne (2014)
The purpose of this applied research is primarily to identify the level of compliance of internal auditors in five selected listed Government Linked Companies (GLCs) to the Institute of Internal Auditors (I I A) Code of Ethics in detecting unethical behaviour and their awareness on unethical practices in the organisation they are working in. Corporate scandals involved GLCs in Malaysia have increased the public queries on the competencies of internal auditors in reviewing the business process of the organisation. Hence, the research will try to identify whether the internal auditors in selected listed GLCs are competent in conducting audit engagement. The researcher also attempted identify whether the internal auditors in selected listed GLCs are aware on unethical practices/behaviour in the organisation they are working in. The results of the research shows that there is some evidence to indicate that internal auditors of the five selected listed GLCs are aware about the unethical practices in their organisation. The conclusion of this study shows that the internal auditors in five elected listed GLCs hold high level of compliance to the HA’s Code of Ethics in conducting audit engagement and identifying unethical practices. However, the findings suggest that the internal auditors should attend training and courses organised by the IIA, MACC and ACFE to increase and improve their knowledge on ethics and fraud in corporate sector.